Estimated impacts of climate warming on California water availability under twelve future climate scenarios - Zhu, Tingju; Jenkins, Marion W.; Lund, Jay R. (Wiley, 2005)
Spatially disaggregated estimates of over 131 streamflow, ground water, and reservoir evaporation monthly time series in California have been created for 12 different climate warming scenarios for a 72-year period. Such disaggregated hydrologic estimates of multiple hydrologic cycle components are important for impact and adaptation studies of California's water system. A statewide trend of increased winter and spring runoff and decreased summer runoff is identified. Without operations modeling, approximate changes in water availability are estimated for each scenario. Even most scenarios with increased precipitation result in less available water because of the current storage systems' inability to catch increased winter streamflow in compensation for reduced summer runoff. The water availability changes are then compared with estimated changes in urban and agricultural water uses in California between now and 2100. The methods used in this study are relatively simple, but the results are qualitatively consistent with other studies focusing on the hydrologies of single basins or surface water alone.